The Crowing Political Matriarchy in Homa Bay County (1963-2022) - Orondo, John Akumu; Budi, Nashon Budy; Okoth, George Odhiambo; Onjala, Isaya Oduor (Journal of Historical Studies, 2023)
Purpose: Crowing Political matriarchy in Homa Bay describes the female's political take over as an impact of the prolonged pursuit of gender equality in Kenya. The takeover is due to policy frameworks intended to address gender gap. While these policy frameworks have been instrumental, historical aspects relating to gender egalitarianism has been underscored to providing elaborate intervention on gender inequality. This paper investigated the impact of the pursuit of gender egalitarianism amidst the survival of patriarchy in Kenya with specific reference to Homa-Bay County since 1964. Methodology: Study is guided by Patriarchal Theory of Robert Filmer which highlights how patriarchal ideology elevated men to superior positions. In the contrary, policy framework; legislative, institutional, and administrative interventions adopted towards gender egalitarianism appear to bear fruits in Homa Bay. A historical research design was applied together with non-probability sampling methods and procedures to identify informants during the study. Other primary data was gathered from the National Archives while secondary data were collected from theses, journal articles, books, and other publications from the internet, university, and other libraries. The data collected has been thematic analysis based of period. The findings may guide policy makers to review and re-assess the impact of the strategies established in the pursuit of gender egalitarianism. Paper deals with the state of gender and political transformation in Homa-Bay County since 1992. Findings: Publication indicates that, legislative, institutional, and administrative interventions adopted in Kenya challenge the patriarchal legitimacy and political entitlement. Unique Contribution to Theory, Policy and Practice: This treatise reports that the gender egalitarian policies and practices make political voices of females in Homa Bay to crow louder than men. Female political voices in Homa Bay began with Asiyo and Bondo who were elected Member of Parliament and councilor respectively in 1980's. Nevertheless, the gender egalitarian policies have been legalized by the Kenya constitution 2010 to the advantage of females leading to the pinnacle of political matriarchy in Homa Bay.